The world trading system after Cancún, or: How the rhetoric of the development round rebounded on the industrialized countries... - Klaus Liebig (Deutsches Institut für Entwicklungspolitik (DIE), 2003)
International trade increases worldwide growth and improves the chances of successful poverty reduction. A development round could reinforce this potential.Development scholars largely agree on what would constitute a development round: improved market access for developing countries, no negotiations on investment and competition rules in the current round, additional support for developing countries in the field of trade-related capacity-building. In contrast to their own rhetoric, however, trade policy makers in industrialized countries do not feel obliged by this consensus. It is therefore they who bear the main responsibility for the failure of Cancún.In Cancún the developing countries successfully presented themselves as an articulate group with the potential to block multilateral trade negotiations. It remains to be seen whether they will use their new-won scopes of action to take a hand in constructively shaping the world trading system. This will depend largely on newly industrializing countries (NICs) and anchor countries like India, China, or Brazil.The conference's failure does not mean a success for developing countries since they failed to achieve their trade-policy goals. What remains is the hope that the shock of Cancún will lead to a greater willingness to compromise, above all on the part of the industrialized countries, but also on the part of NICs and anchor countries, with a view to giving the WTO a more development-friendly shape. If this fails, the multilateral trading system would be in serious trouble.
Keywords: 330